PENERAPAN MODEL PROJECT BASED LEARNING BERBASIS PLATFORM QUIZIZZ UNTUK MENINGKATKAN PEMAHAMAN KONSEP DAN KEMAMPUAN BERPIKIR KRITIS SISWA SEKOLAH DASAR - Dinda Widyastika; Muhammad Dekar Nasution; Zulvia Misykah (Jurnal Genta Mulia, 2025)
The purpose of this study was to describe learning activities, changes in students' critical thinking skills and conceptual understanding after the implementation of the Problem-Based Learning (PBL) model, and students' responses to the model on energy material. The study used a pre-experimental approach with a one group pretest-posttest design, involving 25 fifth grade elementary school students as participants. Data were collected through observation, tests, and questionnaires, then analyzed using quantitative descriptive techniques. The results showed that the implementation of learning was in the very good category, with an average score of 4 during two weeks of implementation. Students' critical thinking skills increased significantly, as seen from the N-Gain value with a high category in 25 students and a moderate category in 1 student. In addition, the questionnaire showed that students' responses to learning were very positive with an average score of 90.37. From these results, it can be concluded that the implementation of the Problem-Based Learning model is effective in improving students' critical thinking skills on energy material. These findings also enrich the science learning literature and are expected to be a reference for teachers in efforts to improve the quality of learning and student learning achievement, especially in developing critical thinking skills in the classroom.